Relasi Wabah dengan Tindakan Destruktif dalam Al-Qur’an - Syachirul A'dhom Al-Fajri Irul (Wasathiyyah, 2022)
When the corona virus hit almost all corners of the earth, there was an assumption that this virus was a form of God's wrath against the injustice that befell some groups of Muslims. although it is true that in various verses Allah tells of the punishment that was revealed to the previous people as a sanction for the destructive actions they did. however, even if the assumption is true, in many explanations it is also explained that Allah is most merciful, most merciful even to those who commit sins, and Allah's mercy is far wider than His punishment. For this reason, in addition to testing these assumptions, this paper also wants to offer a new perspective in reading the verses of the Koran which narrate about plagues, disasters, punishments, and deviations, namely the point of view of grace. Thus, this research method is included in library research, because the research focuses on examining three stories of the previous people, namely the Pharaohs, the Samuds and the 'Ad who were given the punishment of plague and plague as their transgressions.